BANK COMPETITION AND FINANCIAL STABILITY IN NIGERIA - Ariyibi, Mayowa Ebenezer; Agbatogun, Taofeek Osidero; Soyemi, Kenny Ade (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2024)
Introduction: The study examined the impact of bank competition on the financial stability of selected deposit money banks in Nigeria. The study employed panel data (secondary data) that was collected from 2019 to 2023 (both years inclusive). Methods: The panel regression analysis was employed to determine the relationship between the outcome variables and explanatory variable, taking decisions from the Huasman test. Results The findings of the study from objective one revealed that the Herfindahl-Hirchman loan Index has a positive significant effect on capital adequacy ratio along with diversification ratio and bank size, which are control variables. It also has a negative significant effect on capital adequacy ratio. Objective two revealed that the Herfindahl-Hirchman Deposit Index diversification ratio and bank size have a positive significant effect on non-performing loans in Nigeria. Conclusion and suggestion: Based on the findings, it therefore recommended that deposit money banks should diversify their loan portfolio across sectors and customer types to mitigate a concentration risk in the deposit money banks. Reallocating capital from less diversified or larger loans to smaller, more diversified segments of the portfolio would spur the level of competition accuracy of the banks.